Análise de patologias geradas na interface estrutura pré-moldada e estrutura convencional: estudo de caso - Barbosa, João Antonio Lara (2014)
For civil engineering construction Works to finish within the estimated timeline, it is often necessary the use of techniques that optimize the production time. One of the techniques is the use of pre-molded structures along with conventional concrete structures. With the intent of analyzing the pathologies that occurs in this interface, the current work does a case study in a large residential site at the city of Curitiba - PR. The analyzed samples displayed chips, cracks, fissures and concreting flaws, most of the times caused by execution flaws followed by project flaws. To avoid these kinds of pathologies, it is suggested an investment in more qualified work labor and in the case of execution errors, a better compatibility of the projects. The importance of avoiding such pathologies is due to the fact of the occurrence of aesthetical, functional and even structural problems, putting the sites at risk, compromising their durability and the safety of the location.